Developing an instrument to measure patient satisfaction with nursing care in Greece - Merkouris, Anastasios; Yfantopoulos, John N.; Lanara, Vassiliki A.; Lemonidou, Chryssoula (My University, 1999)
Aim The main purpose of this study was to develop a reliable and valid instrument to measure patient satisfaction with nursing care. Background The interest in patient satisfaction is intense but there is an absence of instruments with proper psychometric properties. Methods A methodological exploratory design was employed with three phases: content development and critique, pilot study (N=15) and final tryout (Í=103). Findings The reliability coefficient for the whole scale was high (α=0,94). An exploratory factor analysis revealed six factors, explaining 68.8% of the variability. The first three factors referred to interpersonal relationships and available time, technical competence and response, and information. The qualitative data facilitated the interpretation of the quantitative data, increased the validity of the scale and gave useful information for improvements. Conclusions Overall, the psychometric properties of the instruments were satisfactory but there is a need for continuous evaluation and verification of other studies.